Analisis Kesulitan Belajar dalam Pembelajaran Daring Pada Muatan IPA di Sekolah Dasar - Shofia Novitasari; Deka Setiawan; Siti Masfuah (WASIS : Jurnal Ilmiah Pendidikan, 2022)
This study aims to analyze learning difficulties in online learning on science content during the pandemic at SDN Wegil Sukolilo Pati.This study uses a qualitative research approach with a descriptive type of research. Data collection carried out by researchers includes observation, interviews, and documentation techniques by collecting relevant sources and then analyzed using data cards. The research was carried out at SDN Wegil Sukolilo Pati using research subjects, namely the fifth grade teacher and 3 fifth grade students with a record of 1 student who has high ability, 1 student who has moderate ability, and 1 student who has low ability.Based on the results of research that has been carried out in class V SDN Wegil Sukolilo Pati, it can be concluded that the implementation of learning is in accordance with Circular Letter Number 3 of 2020 and the learning process in class utilizing digital technology used is WhatsApp Grub where there are difficulties in learning in learning thematic content of IPA. There are two factors that cause students to have learning difficulties, namely internal and external factors. Internal factors that influence it: 1) lack of student motivation in online learning, 2) lack of student attention in the learning process, 3) students' slowness in understanding the material. While the external factors that influence it are: 1) Students who do not have their own facilities in supporting the learning process, namely cellphones, 2) the influence of friends in the community who always play.